MtING2 encodes an ING domain PHD finger protein which affects Medicago growth, flowering, global patterns of H3K4me3, and gene expression. (17th October 2022) - Jaudal, Mauren; Mayo‐Smith, Matthew; Poulet, Axel; Whibley, Annabel; Peng, Yongyan; Zhang, Lulu; Thomson, Geoffrey; Trimborn, Laura; Jacob, Yannick; van Wolfswinkel, Josien C.; Goldstone, David C.; Wen, Jiangqi; et al.
SUMMARY: Flowering of the reference legume Medicago truncatula is promoted by winter cold (vernalization) followed by long‐day photoperiods (VLD) similar to winter annual Arabidopsis. However, Medicago lacks FLC and CO, key regulators of Arabidopsis VLD flowering . Most plants have two INHIBITOR OF GROWTH ( ING ) genes ( ING1 and ING2 ), encoding proteins with an ING domain with two anti‐parallel alpha‐helices and a plant homeodomain (PHD) finger, but their genetic role has not been previously described . In Medicago, Mting1 gene‐edited mutants developed and flowered normally, but an Mting2‐1 Tnt1 insertion mutant and gene‐edited Mting2 mutants had developmental abnormalities including delayed flowering particularly in VLD, compact architecture, abnormal leaves with extra leaflets but no trichomes, and smaller seeds and barrels. Mting2 mutants had reduced expression of activators of flowering, including the FT ‐like gene MtFTa1, and increased expression of the candidate repressor MtTFL1c, consistent with the delayed flowering of the mutant. MtING2 overexpression complemented Mting2‐1, but did not accelerate flowering in wild type. The MtING2 PHD finger bound H3K4me2/3 peptides weakly in vitro, but analysis of gene‐edited mutants indicated that it was dispensable to MtING2 function in wild‐type plants. RNA sequencing experiments indicated that >7000 genes are mis‐expressed in the Mting2‐1 mutant, consistent with its strong mutant phenotypes. Interestingly, ChIP‐seq analysis identified >5000 novel H3K4me3 locations in the genome of Mting2‐1 mutants compared to wild type R108. Overall, our mutant study has uncovered an important physiological role of a plant ING2 gene in development, flowering, and gene expression, which likely involves an epigenetic mechanism. Significance Statement: The timing of flowering is important for plant adaptation and crop productivity, but knowledge on how this is regulated in legumes is limited. Here, we report the functional characterization of MtING2 and show that it is important in regulating plant architecture and flowering time in the model legume Medicago truncatula, providing evidence of the physiological role of an ING‐like gene in plants.